2022
DOI: 10.3389/fddsv.2022.983030
|View full text |Cite
|
Sign up to set email alerts
|

Current advances in our understanding of circular RNA (circRNA) in Alzheimer’s disease (AD); the potential utilization of synthetic circRNAs as a therapeutic strategy in the clinical management of AD

Abstract: Current advances in our understanding of circular RNA (circRNA) in Alzheimer's disease (AD); the potential utilization of synthetic circRNAs as a therapeutic strategy in the clinical management of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…CircRNAs exhibit cell-specific, tissue-specific and developmental stage specific expression patterns with high stability due to the lack of free ends typically targeted by 3′ and 5′ exoribonucleases and have a half-life of more than 48 h compared to linear transcripts with half-life of ~6 h ( Huang et al, 2017b ). Furthermore, circRNAs exhibits distinct disease-specific characteristics under different pathological states which makes them promising therapeutic targets as well as potential diagnostic, predictive, and prognostic biomarkers for many incapacitating human diseases ( Verduci et al, 2021 ; Zhao et al, 2022 ). Numerous ncRNAs have been reported to regulate cell death processes including autophagy, apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CircRNAs exhibit cell-specific, tissue-specific and developmental stage specific expression patterns with high stability due to the lack of free ends typically targeted by 3′ and 5′ exoribonucleases and have a half-life of more than 48 h compared to linear transcripts with half-life of ~6 h ( Huang et al, 2017b ). Furthermore, circRNAs exhibits distinct disease-specific characteristics under different pathological states which makes them promising therapeutic targets as well as potential diagnostic, predictive, and prognostic biomarkers for many incapacitating human diseases ( Verduci et al, 2021 ; Zhao et al, 2022 ). Numerous ncRNAs have been reported to regulate cell death processes including autophagy, apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Later on researchers revealed the significance of cirRS-7/miR-7/UBEA2 axis in AD. They reported that down-regulation of ciRS-7 in AD contributed to an up-regulation of miRNA-7 which in turn down-regulated an autophagic, phagocytic protein essential in the clearance of neurotoxic amyloid-beta (Aβ) peptides namely ubiquitin protein ligase A (UBE2A; Zhao et al, 2022 ). It has been suggested that the deregulation of circRNA signaling is involved in blood–brain barrier disruption, angiogenesis, inhibition of pro-inflammatory signaling, apoptosis, autophagy disruption and alteration of cognitive functions in both acute and chronic CNS injury ( Zhao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…“ Synthetic circular RNA (circRNA) as a therapeutic strategy for Alzheimer's disease (AD) ” (Zhao et al, 2022 ). Synthetic circRNAs have recently been identified as a potential therapeutic strategy for AD.…”
mentioning
confidence: 99%
“…This hinders the degradation of amyloid-beta (Aβ) peptides. Zhao et al ( 2022 ) proposed synthetic circRNAs as a potential treatment for AD and other neurodegenerative diseases.…”
mentioning
confidence: 99%